Osteoartrit ile ilişkili Genu Varum ve Genu Varum'um diz eklemi morfolojisine etkisi - Al, Ömer Selim (My University, 2023)
Tezin Başlığı: Osteoartrit ile İlişkili Genu Varum ve Genu Valgum’un Diz Eklemi Morfolojisine Etkisi Amaç: Bu çalışmanın amacı osteoartit hastalığı ile birlikte genu varum ve genu valgum’u olan bireylerin diz ekleminde bulunan menisküs ve cruciate ligamentlerin morfometrik ölçümlerini yapmak, ölçümler sonucunda bu yapıların sağlıklı bireylere göre nasıl değişim gösterdiğini ortaya koymaktır. Gereç ve Yöntem: Çalışmamız retrospektif olarak planlanmış olup, diz bölgesinde cerrahi öyküsü bulunmayan ve yaşları 50 ile 67 arasında değişen, toplam 112 katılımcının MR görüntüleri üzerinden gerçekleştirilmiştir. Çalışmamıza dâhil edilen bireylerin sağ ve sol bacaklarında, meniscus medialis ve lateralis’in anteroposterior uzunluğuna, ön ve arka boynuz sagittal yüksekliklerine, lig. cruciatum anterior ve posterior uzunluğuna bakılmıştır. Elde edilen tüm veriler, sağlıklı insanlar ile genu varum ve genu valgum deformiteleri arasında karşılaştırılmıştır Bulgular: Yapılan çalışma sonucunda, meniscus medialis’in anteroposterior uzunluğu sağlıklı bireylerde, genu varum ve genu valgum deformitelerinde ortalama olarak sırasıyla 40,15 mm, 41,61mm, 39,48mm; meniscus lateralis’in anteroposterior uzunluğu sırasıyla 31,54 mm, 31,86 mm, 32,10 mm olarak ölçülmüştür. Meniscus medialis’in ön ve arka boynuz sagittal yüksekliği sırasıyla ortalama olarak 5,3 mm, 5,69 mm, 5,28 mm, 6,23 mm, 5,16 mm, 5,46 mm olarak ölçülmüş olup; meniscus lateralis’in sırasıyla 5,25 mm, 5,68 mm, 5,35 mm, 6,38 mm, 5,17 mm, 5,46 mm olarak ölçülmüştür. Lig. cruciatum anterior’un uzunluğu sırasıyla ortalama olarak; 38,49 mm, 38,48 mm, 37,48 mm olarak, lig. cruciatum posterior’un uzunluğu sırasıyla ortalama olarak 40,42 mm, 39,27 mm, 41,5 mm olarak ölçülmüştür. Sonuç: Sağlıklı kişiler ile karşılaştırıldığında genu varum ve genu valgumlu bireylerde diz eklemi morfolojisinde anlamlı değişiklikler meydana gelmiştir.

Title of thesis: Effect of Genu Varum and Genu Valgum on Knee Joint Morphology Associated with Osteoarthritis Objective: The aim of this study is to make morphometric measurements of the meniscus and cruciate ligaments in the knee joint of individuals with genu varum and genu valgum together with osteoarthritis disease and as a result of the measurements to reveal how these structures change compared to healthy individuals. Material and Method: Our study was planned retrospectively, and it was carried out on the MRI images of a total of 112 participants, aged between 50 and 67, who had no history of surgery in the knee region. In the right and left legs of the individuals included in our study, the anteroposterior length of the meniscus medialis and lateralis, the sagittal heights of the anterior and posterior horns, lig. cruciatum anterior and posterior lengths were examined. All obtained data were compared between healthy people and genu varum and genu valgum deformities. Results: In healthy individuals, in genu varum and genu valgum deformities the anteroposterior length of the meniscus medialis was found to be 40,15 mm, 41,61 mm, 39,48 mm and the anteroposterior length of meniscus lateralis was measured as 31,54 mm, 31,86 mm, and 32,10 mm, respectively. The anterior and posterior horn sagittal heights of the meniscus medialis were respectively measured as 5,30 mm, 5,69 mm; 5,28 mm, 6,23 mm; 5,16 mm, 5,46 mm on average; while those of the meniscus lateralis were respectively measured as 5,25 mm, 5,68 mm, 5,35 mm, 6,38 mm, 5,17 mm and 5,46 mm. The average length of the anterior cruciate ligament was measured as 38,49 mm, 38,48 mm, 37,48 mm and the average length of the posterior cruciate ligament was measured as 40,42 mm, 39,27 mm, 41,50 mm, respectively. Conclusion: Significant changes in knee joint morphology occurred in genu varum and genu valgum subjects compared to healthy subjects.
Effect of Genu Varum and Genu Valgum on knee joint morphology associated with osteoarthritis
Keywords: Diz eklemi; Eklem hastalıkları; Genu Valgum; Genu varum; Joint diseases; Knee joint; Morfoloji Osteoartritis; Morpholgy; Osteoartrit; Osteoartritis